The occurrence of unpigmented mature oocytes in Hypsiboas (Anura: Hylidae) - Nali, Renato C. (2014)
The genus Hypsiboas is composed of 90 species distributed in Central and South America from Nicaragua to Argentina, as well as on Trinidad and Tobago (Frost 2014). Previous studies on the reproductive biology of species in this genus have reported that female mature oocytes or eggs generally have pigmented animal poles (Tab. 1), which has been generally suggested as a protection of the exposed embryos from solar radiation (Wells 2007).